Pemanfaatan Penginderaan Jauh dan Sistem Informasi Geografis untuk Pemetaan Distribusi Spasial Penyakit Demam Berdarah Dengue (DBD) (Sanitasi: Jurnal Kesehatan Lingkungan, 2009)
Nowadays, the development of remote sensing method has capability for ex-tracting data of environmental factors which are influencing the exictence of breeding places of Aedes aegypti as vector mosquito of Dengue Hemorrhagic Fever (DHF). The output of remote sensing is subsequently used as input of GIS (Geographical Information System) to analyze susceptibility areas of DHF. The aim of the research was to explore the advantage of remote sensing and GIS for area susceptibility mapping on this disease based on some parameters such as: land-use, population density, river, temporary waste disposal sites, and the characteristic of Aedes aegypti prerequisite condition. Scoring is the method used in this research to analyze those parameters. The results shows that extraction land-use from IKONOS image data produced 88 % of accuracy. Furthermore, the map produced from the method shows that 35.28 % (1207,68 ha) and 25,62 % (876,99 ha) area of Depok sub-district, in Sleman regency, DIY province, has medium and high susceptibility of DHF, respectively.